Faecal Calprotectin in Differentiating Inflammatory Bowel Disease (IBD) from Irritable Bowel Syndrome (IBS) (Bangladesh Medical Journal, 2021)
Inflammatory bowel disease (IBD) is a chronic idiopathic inflammatory disorder of the gastrointestinal tract with relapsing and remitting course. Irritable bowel syndrome (IBS) is a gastrointestinal disorder characterized by altered bowel habit in association with abdominal discomfort and pain. Faecal biomarker may be used an accurate tool in the differentiation of IBD and IBS. The aim of this study was to measure faecal calprotectin (FC) level in patients with IBD and IBS and compare between them. This cross-sectional observational study conducted at the department of Gastroenterology, BSMMU, Dhaka, Bangladesh. Patients with IBD were diagnosed on the basis of compatible history, clinical examination, laboratory, radiological and endoscopic findings, where IBS patients were selected by using the Rome IV criteria. Quantitative faecal calprotectin enzyme-linked immune sorbent assay (ELISA), BÜHLMANN Quantum Blue® test was done and compared between IBD and IBS patients. In this study, Ninety (90) patients were enrolled, 45 patients with IBD and 45 patients with IBS. Mean age of the IBD patients was 32.24±9.76 years and IBS patients was 33.80±9.70 years. There were 28 (62.2%) male and 17 (37.8%) female patients with IBD and 30 (66.7%) male and 15 (33.3%) female patients with IBS. We found faecal calprotectin ( FC) level was 445.68 ± 237.35µg/g in IBD patients and 39.16 ± 17.31µg/g in IBS patients. There was a significant difference of faecal calprotectin level between IBD and IBS patients (p-value < 0.001). The sensitivity and specificity of faecal calprotectin to differentiate IBD from IBS was 91.1% and 86.7% respectively. The test accuracy was 88.9%. Area under ROC was 0.959 (95% CI, 0.909 to 1.0). This study showed that faecal calprotectin appears to be clinically useful, non-invasive, rapid and reliable marker to differentiate IBD from IBS.Bangladesh Med J. 2021 January; 50(1) : 15-22